Lightwave propagation in microstructured optical fibers - Yan, Min (2008)
The first optical fiber with an array of air cylinders running along its axis was fabricated by Knight et al. in 1996. It has been a new era for fiber optics ever since. Such fibers can be broadly referred to as microstructured optical fibers (MOFs). Many properties of such fiber, such as dispersion, birefringence, nonlinearity and bending loss etc, can be tailored beyond what we can obtain in a conventional step-index fiber. Later experiments further achieved air-guiding with a periodic air-silica cladding. Such guidance in certain ways requires us to re-define what an optical fiber is.